O impacto da silvicultura na diversidade e grupos funcionais de formigas no cerrado - Aguiar, Jonas José Mendes (2022)
Deforestation is one of the greatest threats to the maintenance of the world's biodiversity and represents a major global concern. This type of change represents the most substantial human impact on the ecosystem. Among the causes of deforestation, forestry stands out, which in Brazil occupied about 7.83 million hectares in 2018, producing about 91% of the wood used in the local industry. There is a growing debate in the scientific community about planted forests, where it is mainly discussed whether or not they can have value in the conservation of biodiversity. In summary, the debate is still multipurpose and still lacks more detailed and conclusive research. This thesis seeks to assist in the understanding and elucidation of problems related to the potential of using forestry in the conservation of biodiversity. Therefore, the general objective of this thesis was to evaluate the efficiency of Eucalyptus spp. as temporary shelter areas for diversity, through the analysis of attributes of ant assemblages. Specifically, using ants as a model, we sought to understand: (1) how the temporal dynamics of the richness and composition of species and functional groups of ants occur in eucalyptus areas of different ages and in different stages of production; (2) how the edge effect is established in areas of a forest phytophysiognomy of the Cerrado, the Cerradão and areas converted into eucalyptus plantations. In the first chapter we observed that: the increase in the age of the stands did not affect the analyzed parameters. Although the pre-cutting age eucalyptus plantations showed lower species richness than the Cerrado natural areas, the cutting-age eucalyptus plantations did not show any difference in species richness with the pre-cutting or pre-cutting areas. natural areas of Cerrado. Regarding species composition, the pre-cut and cut areas of eucalyptus plantations were similar to each other, but they differed from the natural areas of Cerrado. With regard to functional groups, there was no difference in richness and composition between areas. None of the response variables studied (locations, landscape and proximity) were influenced by the explanatory variables considered. In the second chapter, we observed that the species richness of epigean ants in the eucalyptus and Cerrado areas was not affected by the distance from the edge. Only the richness of arboreal ants in the Cerrado areas showed a negative relationship with the distance from the edge. For the composition, the only group that presents a composition difference between edge and interior are epigeic ants in Cerrado areas. Arboreal reserve ants in Cerrado, or arboreal and epigeic ants in eucalyptus plantations, have similar border and interior composition. The species richness of arboreal and epigeic ants in eucalyptus and Cerrado areas was not related to canopy cover. Our results, in general, explain the long-term impact of eucalyptus silviculture on biodiversity, reducing richness and altering species composition, functioning in a way as a barrier preventing the recovery of biodiversity.